2021
DOI: 10.1080/08856257.2021.1872843
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian students’ experiences of homeschooling during the COVID-19 pandemic

Abstract: Norwegian teachers and school leaders had to organise and provide homeschooling for their students from March to May 2020 due to the COVID-19 pandemic. A survey conducted in May 2020 examined lower secondary school students' experiences of distance learning. How students at different levels of academic achievement (based on grades) experienced homeschooling was compared to comparable findings from a survey conducted on students from the same schools during the autumn of 2018. The findings indicate that student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
(23 reference statements)
4
19
0
7
Order By: Relevance
“…Third, not surprisingly, children with poorer academic achievement before the pandemic generally have weaker motivation to learn during school closures. This mirrors a recent finding by Maelan et al (2021), who observed that low-(vs high-) achieving students in Norway generally exhibited lower efforts and self-efficacy throughout the pandemic. Together, these findings highlight that low-achieving students tend to suffer more from COVID-19-related school closures and that these children may require greater and more frequent assistance from parents/ teachers to make progress in their learning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Third, not surprisingly, children with poorer academic achievement before the pandemic generally have weaker motivation to learn during school closures. This mirrors a recent finding by Maelan et al (2021), who observed that low-(vs high-) achieving students in Norway generally exhibited lower efforts and self-efficacy throughout the pandemic. Together, these findings highlight that low-achieving students tend to suffer more from COVID-19-related school closures and that these children may require greater and more frequent assistance from parents/ teachers to make progress in their learning.…”
Section: Discussionsupporting
confidence: 88%
“…Since the pandemic began in early 2020, much research has taken place to shed light on how parents and children worldwide coped with remote learning. For instance, Maelan et al (2021) explored how Norwegian students at various levels of academic achievement differed in their remote learning experience; Dong et al (2020) surveyed how Chinese parents' attitudes towards online learning affected their children's education during the pandemic; Parczewska (2020) investigated how parents in Poland coped with the demands from homeschooling. Although these studies were conducted in different parts of the world, they all noted that school-aged children have difficulty maintaining motivation during remote learning.…”
Section: Introductionmentioning
confidence: 99%
“…The research in databases retrieved 23,039 publications, from which 3515 were duplicates. After screening a total of 19,524 records by title, abstract, and full text, 42 of them were finally considered eligible [ 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (Prisma Flow Chart— Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A consequence of higher levels of disengagement was that students had lower levels of overall motivation (reported in 16 studies, 20%) and lower motivation was identified as being particularly problematic among lower achieving students in some studies (Nusser, 2021;Maelan et al, 2021;Pelikan et al, 2021). Although the explanations put forward for lower motivation among students were diffuse, a number of studies attributed issues with technology and internet connection as explanatory factors (Al Salman et al, 2021;Dema et al, 2021;Hodgen et al, 2020).…”
Section: Lower Motivation and Learning Lossmentioning
confidence: 99%